Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300813
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Telemanipulation in Robotic Assisted Surgery

Abstract: Robotic-assisted Minimally Invasive Surgery (MIS) is adopted more and more as it overcomes the shortcomings of classic MIS for surgeons while keeping the benefits of small incisions for patients. However, introducing new technology oftentimes affects the work of skilled practitioners. Our goals are to investigate the impacts of telemanipulated surgical robots on the work practices of surgical teams and to understand their cause. We conducted a field study observing 21 surgeries, conducting 12 interviews and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
0
16
1
1
Order By: Relevance
“…We acknowledge this list has limitations: surgical tasks greatly vary according to the specialty and specific procedure. Although the observed appropriation uses were consistent among the different surgeons (from study [4]), this list is not exhaustive as there might be other uses yet to be identified. We now review existing bedside robotic endoscopes and their controls.…”
Section: Beyond Intended Use: Endoscope Appropriationmentioning
confidence: 93%
See 4 more Smart Citations
“…We acknowledge this list has limitations: surgical tasks greatly vary according to the specialty and specific procedure. Although the observed appropriation uses were consistent among the different surgeons (from study [4]), this list is not exhaustive as there might be other uses yet to be identified. We now review existing bedside robotic endoscopes and their controls.…”
Section: Beyond Intended Use: Endoscope Appropriationmentioning
confidence: 93%
“…non-robotic) endoscope uses to characterize it. We use observations from a previous study in HCI [4] and hierarchical task decompositions in the literature for different surgical procedures, including: the Nissen fundoplication procedure [31], laparoscopic radical prostatectomy [1] and cholecystectomy [8]. We incorporate a gynecology surgeon with 10 years of laparoscopic surgery experience into our team to provide feedback.…”
Section: Characterizing Endoscope Use: Tasks Analysismentioning
confidence: 99%
See 3 more Smart Citations